Molecular classification and clinical diagnosis of acute-on-chronic liver failure patients by serum metabolomics - Yu, Meng; Zhou, Chao; Tian, Dong; Jia, Hong-Mei; Li, Zhi-Qing; Yang, Chen; Ba, Yuan-Ming; Wu, Hui-Kun; Zou, Zhong-Mei (Journal of pharmaceutical and biomedical analysis, 2021)
•An UPLC-MS metabolomics method was established to analyze serum metabolome of ACLF patients.•10 serum metabolites as potential biomarkers for diagnosis of ACLF patients.•3 serum metabolites for predicting two types of ACLF patients, i.e. DH and CD. Prevalence of acute-on-chronic liver failure (ACLF) patients is growing worldwide, associating with multi-organ failure and high short-term mortality rates. ACLF can be of varying entity manifestation, whereas it remains poorly defined. Traditional Chinese medicine (TCM) stratifies ACLF into two types, damp hot (DH) and cold damp (CD), by seasoned TCM practitioners, for specific treatment with different TCMs. The biggest challenge for the outcome of TCM therapy is the accuracy of diagnosis. However, it is difficult to guarantee it due to lack of the molecule classification of ACLF. Herein, we recruited 58 subjects including 34 ACLF patients (18 DH and 16 CD) and 24 healthy controls, and analyzed serum metabolic profiles using untargeted ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS) metabolomics approach. A total of 10 serum metabolites were found as potential biomarkers for diagnosis of ACLF. Among them, taurochenodesoxycholic acid (N3), glycyldeoxycholic acid (N5) and 12-HETE-GABA (N7), varied between two types of ACLF and can be merged as a combination marker to differentiate CD from DH patients with area under the receiver operating curve (AUC) of 0.928 (95 % CI 0.8–1). CD patients possessed comparatively higher bile acid metabolism and lower arachidonic acid metabolism compared with DH patients. The results provide not only serum molecules for early accurate diagnosis of ACLF patients, but also potential clinical biomarkers for classification of CD and DH types. The findings clarify that molecular markers will be objective criteria for diagnosis of clinical types in TCM practice.